Health Literacy dengan Illness Perception Pada Lansia Diabetes Mellitus - Ari Setyarini, Elizabeth; Claudia Mariana, Erika; Triastusi, Lidwina; Budi, Albertus (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Elderly people who have unhealthy behaviors such as smoking habits, have the perception that the cost of checking burdens the family and are lazy to check their health because they feel healthy, will affect the ability of the elderly to access health information. This study uses a quantitative method with a cross sectional approach, which aims to determine the relationship between health literacy and illness perception in elderly Diabetes Mellitus. The population in this study was 150 with a sample of 117 elderly people with diabetes mellitus who participated in filling out the questionnaire. The HLS-EU-Q16 (Health Literacy Survey Questionnaire) questionnaire was used to measure health literacy and B-IPQ (The Brief Illness Perception Questionnaire) to measure illness perception. The sampling technique of this study used accidental sampling with data analysis using the spearman rho test to determine the correlation of two variables. The results showed that most respondents had sufficient health literacy and some respondents had positive illness perception. Health literacy correlates significantly with illness perception (p < 0.05) and the direction of the correlation is positive, meaning that the higher the health literacy, the higher the Illness Perception. The strength of the correlation of r = 0.571 includes moderate criteria. This study can provide a source of information for the elderly and health workers in maintaining health literacy with various approaches and creating programs that can affect the illness perception of the elderly